Urgensi Penetapan Besaran Deposito Berjangka Jaminan Reklamasi dan Pascatambang oleh Perusahaan Pertambangan Asing di Indonesia - Pratama, Muhammad Bintang; Latifah, Emmy (UIR Law Review, 2019)
The purpose of this paper is to express the urgency of determining the amount of time deposits by foreign mining companies in Indonesia. The application of time deposits is a manifestation of enforcement of environmental protection carried out by foreign mining companies in Indonesia. Disbursement of funds placed in partner banks that have been determined before the issuance of a Mining Business License (IUP) is based on the projected value of mining production profits as a form of environmental protection if real errors are made by foreign mining companies in relation to environmental management. This research is normative through library studies using secondary data sources, namely using primary legal materials, secondary legal materials, and tertiary legal materials. Data analysis and data validation used source criticism related to the theme of time deposits guaranteed for reclamation and post-mining by foreign mining companies in Indonesia. The results of the study indicate that the old method of determining time deposits based solely on the projected value of mining production profits, is something that is not right. This is because the amount of time deposits placed is sometimes not proportional to the level of environmental damage caused as a result of mining production. A new method is needed to determine time deposits that should be based on the level of environmental damage, both during the mining production process until the end of the company's responsibility for the former mining production area as a form of environmental protection and management. Therefore, the determination of the amount of reclamation and post-mining time deposits based on the level of environmental damage caused by the production of foreign mining companies in Indonesia is deemed necessary as a real effort to improve environmental protection and management in the mining sector in Indonesia.